2006
DOI: 10.1080/02699050500487563
|View full text |Cite
|
Sign up to set email alerts
|

A personal intervention substance abuse treatment approach: Substance abuse treatment in a least restrictive residential model

Abstract: The following paper will detail demographic information about alcohol and substance abuse issues in the acquired brain injury (ABI) population. Included in such a review will be a systematic presentation of the current data on the incidence of such issues as well as a comprehensive treatment model with outcome data provided. Pre- and post-test measures of separate functional outcome areas were employed to assess the effects of the treatment package. The paper will document the core elements of a substance abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…An observational prepost study design was used due to the obvious practical and ethical concerns of withholding or delaying treatment required for a randomized control design. In addition, in a previous study [28], repeated pre-treatment measures demonstrated a stable baseline across two assessment periods. Participants in the previous study demonstrated similar levels of severity, age, gender and time post-injury and there is no reason to assume a significant difference in the population between studies, As in previous studies [27,28] the FAOM was used to determine change from admission to discharge in areas of residential status, level of supervision, community integration, self-managed behaviours, level of awareness and vocational or productive activity.…”
Section: Current Studymentioning
confidence: 81%
See 1 more Smart Citation
“…An observational prepost study design was used due to the obvious practical and ethical concerns of withholding or delaying treatment required for a randomized control design. In addition, in a previous study [28], repeated pre-treatment measures demonstrated a stable baseline across two assessment periods. Participants in the previous study demonstrated similar levels of severity, age, gender and time post-injury and there is no reason to assume a significant difference in the population between studies, As in previous studies [27,28] the FAOM was used to determine change from admission to discharge in areas of residential status, level of supervision, community integration, self-managed behaviours, level of awareness and vocational or productive activity.…”
Section: Current Studymentioning
confidence: 81%
“…A more recent study by McMorrow et al [27] outlined specific treatment components of pro-active behavioural treatment to promote rehabilitation gains and demonstrated durable outcomes in level of independence, community participation, behavioural self-management, level of awareness and vocational status at 1-year follow-up, as measured by the Functional Area Outcome Menu (FAOM) in a small groups design. Hensold et al [28] demonstrated significant treatment effects utilizing the same personal intervention approach to persons with significant substance and behavioural issues also using the FAOM outcome tool.…”
Section: Introductionmentioning
confidence: 97%
“…This finding has significant implications for the delivery of psycho-social drug and alcohol treatment as around half of the treatment population may experience difficulty understanding, remembering and applying information about drug and alcohol misuse to their own situation. Further, it is likely that this same group of people will experience barriers to participating in the daily routines of residential treatment and complying with directions from staff (Hensold et al, 2006;Mantell, 2010). It is not surprising that level of education and cognitive impairment are related.…”
Section: Discussionmentioning
confidence: 93%
“…These factors indicate that people with cognitive impairment are likely to experience difficulty engaging with and participating in substance misuse treatment that is predominantly based on cognitive and behavioural change activities. Further, some of the behaviours described as common features of cognitive impairment, such as poor self-monitoring and self-regulation and dependence/lack of initiative are seen in some treatment modalities to be causes and consequences of addiction thereby ascribing moralistic explanations to behaviours that may be due to an impairment (Goddard, 2003;Hensold et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation